Literature Review: Parenting Style pada Remaja dengan Perilaku Hedonisme - Anisa Rahma Putri; Zakwan Adri (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Parenting style in adolescents with hedonism behavior: Nowadays developments continue to occur so that many changes in technology and learning appear, one of the behaviors that is happening nowadays is hedonism behavior. One that can influence hedonistic behavior is parenting style. Parenting is one of the things that influence how a child's behavior. Hedonism is one of the behaviors of a child that can be caused by how parents raise a child. The purpose of this literature review is to find out what parenting styles lead a child to have hedonistic behavior. The method used is a literature review. The articles used in conducting this literature range from 2017-2022 which were searched for by the online research database. There are several types of parenting styles applied by parents. This study also explains what is the relationship between parenting style and the hedonistic behavior of a child. The results of research that hedonism behavior in a child can be caused by permittive and authoritative parenting styles. If the permittive and authoritative parenting style is high, the possibility of a person's hedonistic behavior will also increase.